The Immigration Law of 1924 - Fairchild, Henry Pratt (Quarterly Journal of Economics, 1924)
Four periods in the history of immigration policy, marked by the years 1830, 1882, 1917, 654. — The act of 1917 and the literacy test, 656. — The act of 1924 and the forces back of it, 659. — Its provisions, 660. — The Japanese question, 664.